2014
DOI: 10.1088/1475-7516/2014/11/025
|View full text |Cite
|
Sign up to set email alerts
|

The time delay in strong gravitational lensing with Gauss-Bonnet correction

Abstract: The time delay between two relativistic images in the strong gravitational lensing governed by Gauss-Bonnet gravity is studied. We derive and calculate the expression of time delay due to the Gauss-Bonnet coupling. It is shown that the time delay for two images with larger space each other is longer. We also find that the ratio of

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Similarly from ( 27), (30) and the condition of nonpositive trace T ≤ 0 , we see that P ′ (r H ≤ r < r γ ) ≤ 0. From this last condition and (31) we have…”
Section: Upper Bound On the Photon Sphere Radiisupporting
confidence: 57%
See 1 more Smart Citation
“…Similarly from ( 27), (30) and the condition of nonpositive trace T ≤ 0 , we see that P ′ (r H ≤ r < r γ ) ≤ 0. From this last condition and (31) we have…”
Section: Upper Bound On the Photon Sphere Radiisupporting
confidence: 57%
“…Even without these Gauss-Bonnet corrections, the ndimensional version of GR is usually studied in astrophysical and theoretical contexts, and in general it is also the case using other alternative gravitational theories. For some works on these topics in EGB or pure GR see [11,26,[28][29][30].…”
mentioning
confidence: 99%
“…These strong deflection lensing can be used to determine different black holes [88][89][90][91][92], naked singularities [93][94][95][96] and wormholes [97][98][99][100][101] as well as test gravity [102,103]. If the source of light has time signals, time delays between the relativistic images can also reveal some information about the lens [104][105][106][107]. Reviews of strong deflection lensing can be found in [108,109].…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, in order to obtain a more comprehensive picture of the photons coupled to the Weyl tensor in the regular phantom black hole, we investigate its time delay in both weak and strong deflection gravitational lensing, which is absent in the previous work [88]. These time-domain signals are important for determining the properties of black holes [89][90][91][92][93][94] and probing new physics [95][96][97][98][99][100][101][102].…”
Section: Introductionmentioning
confidence: 98%